Barriers in Educational Changes - Literature Review - Atroszko, Bartosz (INSTED: Interdisciplinary Studies in Education & Society, 2019)
The article presents a review of a key Polish and English literature about barriers in educational change. The aim of the review was an answer to the following question: what are the main categories of barriers in educational changes in academic papers? For the review purposes three levels of barrier appearance were distinguished: macro, mezzo and micro. At the macro level a state educational policy was most often indicated as well as the paradigm that dominates in education. At the mezzo level the educational policy of local self-government was mentioned as well as the school culture, hyper-innovativeness, organisational and leadership issues, teachers education and resources need for making a change. The micro level includes teachers? resistance against a change, the status of teachers-innovators and teachers?mental incapacitation.